Countering Student Delinquency Through Islamic Religious Education in Senior High School - Marwiyah, St; Alauddin, Alauddin; Arifuddin, Arifuddin; Hasriadi, Hasriadi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This research discusses Islamic Religious Education teachers' strategies to overcome student delinquency at SMA Negeri 3 North Luwu. This research aims to find out (1) the forms of student delinquency, (2) the strategy of Islamic Religious Education teachers in handling student delinquency, and (3) the obstacles faced by teachers in the process. This research methodology is descriptive and qualitative, with data collected through observation, interviews, and documentation. The data were analysed with data reduction, presentation, and verification stages. The results showed that: (1) The forms of student delinquency in SMA Negeri 3 North Luwu are quite varied. These behaviours include being late, leaving class, skipping class, fighting, using electronic devices that violate the rules, and fighting teachers. (2) The strategies used by Islamic Religious Education teachers include preventive and curative measures, such as activating religious activities at school, providing motivation, collaborating with various parties, providing guidance and direction, and imposing punishment. (3) The obstacles teachers face include the large number of students, the lack of cooperation between principals, teachers, and students, and students' uncontrolled use of social media. This research contributes to providing an overview of how in turn, it can provide valuable information for the improvement of education in the future.